The Role of Machine Vision Technology in the Manufacturing of Vehicles in Industry - Pramod Misra, Neha Tiwari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
With the rapid development of machine vision technology, the characteristics of computer vision techniques such as rapidity, precision, and intelligence have gradually been widely used in various fields of modern industry, especially in the automobile manufacturing industry. The three main applications of machine vision in the industrial field are visual measurement, visual guidance, and visual inspection. The visual measurement technology can ensure the quality of the factory products by measuring the key dimensions, surface quality, and assembly effects of the product; the visual guidance technology can significantly improve the manufacturing efficiency and body assembly by guiding the machine to complete automated handling, optimal matching assembly, and precise hole making, etc. Visual inspection technology can monitor the stability of the body manufacturing process, and can also be used to ensure product integrity and traceability, which is conducive to reducing manufacturing costs. It is foreseeable that with the improvement of the performance of core hardware such as cameras, lenses, computers, and the development of software technologies such as image processing and deep learning, the role of vision technology in various fields will become more prominent in the future, and the development space will also be broader